2014
DOI: 10.1016/j.jsps.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Diisocyanate mediated polyether modified gelatin drug carrier for controlled release

Abstract: Gelatin is an extensively studied biopolymer hydrogel drug carrier due to its biocompatibility, biodegradability and non-toxicity of its biodegraded products formed in vivo. But with the pristine gelatin it is difficult to achieve a controlled and desirable drug release characteristics due to its structural and thermal lability and high solubility in aqueous biofluids. Hence it is necessary to modify its solubility and structural stability in biofluids to achieve controlled release features with improved drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Therefore, the applications of the gelatin hydrogel in vivo are limited, due to its poor mechanical properties, rapid degradation rate, and low transition temperatures. To obtain suitable mechanical strength and stable gelatin hydrogel, various chemical crosslinking methods have been used, such as glutaraldehyde [ 14 , 15 ] and diisocyanate [ 16 , 17 ]. However, most of the chemical crosslinkers are toxic, and their use as cell-laden matrices for tissue engineering application is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the applications of the gelatin hydrogel in vivo are limited, due to its poor mechanical properties, rapid degradation rate, and low transition temperatures. To obtain suitable mechanical strength and stable gelatin hydrogel, various chemical crosslinking methods have been used, such as glutaraldehyde [ 14 , 15 ] and diisocyanate [ 16 , 17 ]. However, most of the chemical crosslinkers are toxic, and their use as cell-laden matrices for tissue engineering application is limited.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Hence, it is possible to overcome the poor compatibility and decrease cost of photosensitive polysiloxane prepolymers, and improve the comprehensive performances of the prepolymers by introducing polyether into photosensitive polysiloxane prepolymer molecules.…”
Section: Introductionmentioning
confidence: 99%
“…This result does not indicate that the patients were unsuitable for pericardial pressure after effusion draining, but could be attributed to the first release of 5‐FU or the drug burst release ‐caused reaction. Burst release refers to the transient high‐concentration drug release caused by the residual drugs among the particle microcapsule before the sustained‐release formulation reaches a releasing plateau in the releasing medium or in vivo , which may lead to toxic drug levels in the body [10–12]. Studies have suggested that the preparation should undergo in vitro cleaning before entering the body.…”
Section: Discussionmentioning
confidence: 99%